Penyuluhan Anti-Bullying pada Siswa Sekolah Dasar di Desa Margaluyu dengan Metode Musikalisasi - Noerma Kurnia Fajarwati; Dyah Sotyaningtyas; Ade Jumaiah; Patimah Patimah; Siti Nurhawiyah; Lili Triskomawalat; Anisah Anisah; Susilawati Susilawati (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Anti-bullying counseling for elementary school students in Margaluyu Village aims to increase children's awareness and understanding of bullying behavior and its impacts. Using the musicalization method, this activity combines education with art, making it more interesting and interactive for students. Through relevant songs and creative activities, students are invited to recognize forms of bullying, understand the importance of empathy, and learn strategies to prevent and overcome this behavior. The results of the counseling show increased knowledge and positive changes in attitudes among students towards bullying. It is hoped that this program can be used as a model for other schools in their efforts to create a safe and supportive learning environment. Thus, this activity not only focuses on education, but also contributes to character development and solidarity among students.